Avaliação do Risco de Contaminação de Águas Subterrâneas na Região Oeste da Bahia pelo Inseticida Carbofuran, Empregando os Modelos Attenuation Factor (AF) e Retardation Factor (RF) - Santos, Jorge Luís Oliveira; Leite, Oldair Donizeti (Orbital: The Electronic Journal of Chemistry, 2016)
This work was carried out to study ground water contamination potential by the insecticide carbofuran (2,3-dihydro-2,2-dimethylbenzofuran-7-methylcarbamate), the estimated profile leaching of 0 -10 cm and 10-20 cm the oxisol a soy acreage, corn, and cotton in Barreiras, Western Bahia region. The leaching parameters were assessed employing Attenuation Factor (AF) and Retardation Factor (RF) models, two indices used as groundwater contamination potential indicators. Based on the values for the models, it was found that the total contribution of pesticide reaching the ground, concentrated to 35% at 10 cm depth. Among these, 26% leached to a depth of 20 cm of the soil profile. The results for the models demonstrated the likelihood of contamination of groundwater by leaching of carbofuran.DOI: http://dx.doi.org/10.17807/orbital.v1i1.715